Multiple-Criteria Analysis of Energy Utilization of Coal, Oil and Plant Waste in the Composition of Fuel Mixtures - Vershinina K. Yu. Kseniya Yurievna; Dorokhov V. V. Vadim Valerjevich; Romanov D. S. Daniil Sergeevich; Strizhak P. A. Pavel Alexandrovich (2022, 2022)
Title screen